MEASURES REFERENCES OF ABNT: Instrument for the standardization of clothing products (ModaPalavra e-periódico, 2017)
In order to standardize the units of clothing measurements, ABNT (Brazilian Association of Technical Standards) conducts research for the development of national measures reference in children, male and female segments. The standards of child and male measures are already in place, however, still works for the improvement of a female norm. Regarding the normalization of measures of Brazilian clothing, sought to identify the system methodology adopted for the development of standards of existing measures and to analyze how this information is absorbed by the fashion market. The research was based on bibliographic and documentary survey, considering mainly the standards of Brazilian measures benchmarks and projects these rules had little or no anthropometric study in its methodology. Consequently, it was noticed certain fragility of reference measures currently used, however, the accuracy in sight with the studies that are under development and the possible outcomes that will soon be available for analysis.
Keywords: anthropometry; normalization; clothing